Becoming-social in a networked age - Thomas, Neal (London : Taylor and Francis, 2018)
"This book examines the semiotic effects of protocols and algorithms at work in popular social media systems, bridging philosophical conversations in human-computer interaction (HCI) and information systems (IS) design with contemporary work in critical media, technology and software studies. Where most research into social media is sociological in scope, Neal Thomas shows how the underlying material-semiotic operations of social media now crucially define what it means to be social in a networked age. He proposes that we consider social media platforms as computational processes of collective individuation that produce, rather than presume, forms of subjectivity and sociality."--Provided by publisher.
chapter 1 On the Notion of a Formatted Subject -- chapter 2 The Epistemically Formatted Subject -- chapter 3 The Performatively Formatted Subject -- chapter 4 The Signaletically Formatted Subject -- chapter 5 The Allagmatically Formatted Subject -- chapter 6 Conclusion -- Toward an Enunciative Informatics.
Keywords: Online social networks; Social media